2006
DOI: 10.1002/stab.200610101
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Ermüdungsverhalten von hochfesten Stählen im Rahmen von LIFTHIGH

Abstract: Um den Kerbfallkatalog der neuen europäischen Normung um kranspezifische Kerbdetails und höhere Streckgrenzen zu erweitern, wurden bereits im Forschungsprojekt P 512 der FOSTA verschiedene geometrische Ausführungen der aufgeschweißten Längsrippe sowie fünf unterschiedliche Varianten stumpfgestoßener Bleche aus hochfestem Stahl untersucht. Die daraus gewonnenen Erkenntnisse wurde als Grundlage für weitere Untersuchungen auf europäischer Ebene im Rahmen des ECSC-Forschungsprojekts LIFTHIGH -"Efficient Lifting Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In practice however machining critical details is time consuming, especially for large structures. The German steel journal Stahlbau pays special attention to research on high strength steel in [7,8,9]. A research project relating to the fatigue classification of high strength steel is the project 'Efficient Lifting Equipment with Extra High Strength Steel' (LIFTHIGH), initiated by the ECSC [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice however machining critical details is time consuming, especially for large structures. The German steel journal Stahlbau pays special attention to research on high strength steel in [7,8,9]. A research project relating to the fatigue classification of high strength steel is the project 'Efficient Lifting Equipment with Extra High Strength Steel' (LIFTHIGH), initiated by the ECSC [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, it was found that reduction of the notch factor, which was achieved by machining welds, gives an advantage for very high strength steels. Puthli et al (2006), performed fatigue tests on various butt welded plate specimens with a thickness of 6-8 mm made of S690, S960 and S1100 in the framework of a research program of ECSC. The characteristic fatigue strength of all steel grades was found to be above the recommended values of EN 1993EN -1-9 (2006.…”
Section: Introductionmentioning
confidence: 99%